Congenital bilateral absence of flexor pollicis longus tendon without associated anomalies of thumb hypoplasia: A case report - Kumar, Ritesh; Singh, Naveen Kumar; Kumar, Sanjeev (Indian Journal of Case Reports, 2020)
The human thumb is the most important integral part of our hand because of its unique pattern of development which makes it the most unique digit of the hand. Any deviation from the normal development of the thumb leads to serious malfunction and cosmetic problems. One of the rarest types of anomaly is the congenital bilateral absence of flexor pollicis longus (FPL) tendon without thumb hypoplasia and thenar atrophy. In this paper, we are reporting the case of a 30-year-old girl with the congenital bilateral absence of FPL tendon without any associated anomalies of the thumb hypoplasia. The diagnosis is confirmed if the patient is not able to flex the interphalangeal joint of both the thumbs in the presence of an absence of interphalangeal joint creases. Apart from physical examination, we have also used radiographic and magnetic resonance imaging to diagnose our case.